(untitled) (London Journal of Research In Science: Natural and Formal, 2025)
Starch and xanthan are viscosifying, film-forming polysaccharides obtained from renewable sources. The main objective of this work was to assess the effects of the cassava starch/deacetylated xanthan proportion and reaction time in the crosslinking performed with sodium trimetaphosphate on the Physico-chemical, rheological, structural, thermal, mechanical and barrier properties of resulting hybrid polymeric powder and films. Xanthan deacetylation, performed to improve crosslinking, increased xanthan viscosity and pseudoplasticity. For further crosslinking, the crosslinking agent (SMTP) and the alkalizing agent sodium sulfate (SS) concentration was set at 5% and 3% respectively relative to the total polymeric mass (5%m/v); and according to the Central Composite Rotatable Design (DCCR 22) the starch/deacetylated xanthan proportion and reaction time was varied, totalizing 11 treatments with 3 repetitions at the central point. Physical and chemical features of the crosslinked polymers were checked, as well as films based on the crosslinked hybrid polymers were prepared and tested. Treatments that showed best results were T1 (s/x: 4.5/0.5; 52 min.) and T4 (s/x: 3.5/1.5; 127 min). These resulted in low solubility, thickness and permeability to water vapor, with high tensile strength.